News avoidance in the UK remains high as lockdown restrictions are eased - Fletcher, R; Kalogeropoulos, A; Nielsen, R (Reuters Institute for the Study of Journalism, 2020)
In this RISJ Factsheet we examine again the issue of news avoidance during the coronavirus pandemic in the UK. This is the eighth in a series of ten factsheets based on an ongoing online panel survey of a representative sample of the UK population, fielded from 16 July to 22 July 2020. We find that: (i) levels of news avoidance grew sharply in April and May at the start of lockdown and have broadly remained at high levels since then, (ii) even as the proportion that say COVID-19 is the single most important issue facing the UK today fell from 72% at the end of April, to 51% in mid-July. (iii) Most of those that avoid news about COVID-19 say it is because "it has a bad effect on my mood”, and most COVID-19 news avoiders say that they avoid news on television.